(untitled) (Nigerian Journal of Technology, 2017)
Generally, manual method of re-grinding drills poses the dangers of damage and accidents. This paper reports the method used in the design, fabrication and testing of the drill re-grinding fixture. The fabricated fixture can withstand maximum normal and tangential forces of 121.34 N and 87.76 N respectively. The developed fixture shows it is suitable as work holding device for re-grinding drills bits with diameter of at least 4.5 mm and above without breakage and difficulty. The average time for complete re-grinding is about six minutes (loading and unloading time inclusive) and no injuries were recorded. The grinded surfaces conform to the standard tool geometry for a twist drill. Hence, the use of this drill re-grinding fixture in the engineering workshops obviates the rigor of manual handling of drills during grinding. http://dx.doi.org/10.4314/njt.v36i2.16